A quantitative recovery process of rare earth in bastnaesite leachate for energy saving and emission reduction. (December 2022) - Liu, Chenhao; Zhang, Hepeng; Luo, Bing; Li, Liqing; Sun, Xiaoqi
Graphical abstract: Highlights: A novel enrichment process of bastnaesite leachate has been developed. NLSA has a task-specific precipitation ability for rare earth. The separation coefficient (βRE/Al) reaches 375. The generation of impurity removal residue can be avoided. The process can reduce energy consumption and carbon emission. Abstract: Extraction-precipitation method is a novel separation strategy, a new extraction-precipitant N -lauroyl sarcosine (NLSA) is synthesized in this article. It was found that the extraction-precipitant has a task-specific precipitation ability for rare earth (RE). RE(III) can be recovered quantitatively in the presence of Ca(II), Mg(II), Al(III). When the precipitation rate of RE is 96 %, the precipitation rate of Al is only 6.8 %. The separation coefficient (βRE/Al ) reaches 375, and the precipitation of Ca(II) and Mg(II) is negligible. The solid complex produced in the precipitation process has a large particle size which is easy to be separated. In addition, the precipitation can be completely stripped with 6 mol/L hydrochloric acid, and the REO concentration of stripping solution reaches 255 g/L. After 5 cycles of extraction-precipitation, the specific precipitation of NLSA on RE remains basically unchanged. Mechanism analyses indicate that the extraction-precipitation process is cation exchange. The specificity of the precipitation process can be attributed to the steric hindrance of amide bonds hindering the coordination of Al (III). Finally, a novel enrichment process of bastnaesite leachate is developed to enrich RE, which can effectively remove impurities, so as to effectively avoid the generation of impurity removal residue. Also the enrichment process can reduce energy consumption and carbon emission. The pulverized coal consumption in this process is only 6.25 % of the existing industrial process, and the carbon emission has been decreased by 93.75 %.